Assessment of tidal stream energy's ability to enhance system resilience (Proceedings of the European Wave and Tidal Energy Conference, 2025)
As energy systems transition from centralised, dispatchable power produced by fossil fuel-based technologies, to de-centralised, intermittent renewables, the need for resilient energy system design is becoming ever-more pertinent. This challenge was brought to the forefront during the 2021-22 energy crisis, when the combination of unseasonally low wind resource, and high imported energy prices, resulted in significant increases in the cost of energy that were around an order of magnitude greater than the value of the loss in wind load [1].It is estimated that by 2050, the UK will require up to 116 TWh/year and 502 TWh/year of electricity generated from solar PV and onshore/offshore wind respectively [2]. These projections show other renewables to play a very small part, contributing up to 15 TWh/year. Currently, solar PV, onshore/offshore wind and other renewables provide around 16 TWh/year, 96 TWh/year and 12 TWh/year respectively. Whilst solar and wind are critical as the primary suppliers of renewable energy now and in the future, their intermittency and weather-dependency inevitably bring system resilience risks that require mitigation.The research presented here investigates enhancement to resilient energy system design at times of high system stress, through the uptake of alternative renewable generation technology, focussing on tidal stream energy. Tidal stream provides a different offering to solar PV and wind, since its power generation is independent of weather, predictable far into the future, and reliable in providing power every day, albeit at different levels depending on the timing of spring-neap cycles. This research queries future energy scenarios that rely so heavily solar PV and wind, and so little on alternative, weather-independent technologies.Results are presented from a new energy system model (ESM). The ESM simulates the power flows between power generators, energy storage and load, with these system components linked by the transmission grid that connects 12 nodes across the UK electricity network. A range of tidal stream capacities are investigated, to establish the impact(s) of replacing a relatively small proportions of solar PV and onshore/offshore wind, acknowledging that solar PV and wind will always remain the primary sources of renewable power. The ESM solves the linear optimal power flow equations using the Gurobi solver, to minimise the cost of hourly dispatch over a full year, adopting a similar modelling framework to that set out by Pennock et al., (2023) [3]. The year 2022 was chosen to simulate the recent energy crisis, thereby stress testing the energy system during a period when known significant cost impacts were incurred as a result of high imported energy prices and low wind generation.References[1] UK Government, 2023, £40 billion spent protecting families and businesses from energy costs, Available online: https://www.gov.uk/government/news/40bn-spent-protecting-families-and-businesses-from-energy-costs [2] Energy System Operator, 2024, Future Energy Scenarios: Pathways at a Glance, Technical report[3] Pennock S et al., 2023, A modelling framework to quantify the power system benefits from ocean energy deployments, Applied Energy, 121413